Analisis Nilai Tambah (Value Added) serta Pengendalian Stok Bahan Baku Kopi pada Agroindustri â€œMahkotaâ€ di Kabupaten Ogan Komering Ulu - Suryanawati, Suryanawati; Pusvita, Ema; Ogari, Putri Ayu (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2020)
Research with the title: "Control Analysis of Raw Material Availability and Value Added Coffee in Agroindustry" Mahkota "in Ogan Komering Ulu District". This research has the aim of knowing the optimal control of dry bean coffee raw material supplies in the "crown" agro-industry in Ogan Komering Ulu District, and to find out how much value-added from dry bean coffee to ground coffee in "crown" agro-industry in Ogan Komering Ulu District. This study uses a simple random sampling method. The sample used 1 agroindustry of MSME Ground coffee with a total sample of 17 people, 2 main respondents were business owners and 15 workers. With the data analysis method using the added value of the Hayami Method. Research yields were the order level of dry bean coffee raw materials in the Mahkota Coffee Powder Agroindustry is not economical. The raw material requirement for dry bean coffee is 100 kgs per order, while the number of economic orders using the EOQ method is 90.3 kgs and the reorder rate of dry bean coffee raw materials in the Mahkota Coffee Powder Agroindustry is efficient because the ROP value is smaller than the EOQ value Ground coffee products in the crown powder Agroindustry provide positive added value. Processing of dry coffee beans into ground coffee provides an added value of Rp20,900 with a value-added ratio of 45.04%